Phylogenomics and a new classification of the tropical genus Heliconia L. (Monocots, Zingiberales, Heliconiaceae) - W. John Kress; Tomáš Fér; Mónica M. Carlsen (PhytoKeys)
Members of the genus Heliconia L. (Heliconiaceae) have evolved complex interactions with both insect herbivores and hummingbird pollinators in tropical forests and secondary growth where they are abundant and diverse. Many of these same species have also been cultivated as ornamentals around the world for hundreds of years because of their extraordinary colors and forms. Because of the large size, fleshy nature, and tropical distribution, and despite a long taxonomic history, the classification and phylogenetic relationships of species of Heliconia have not received sufficient attention to date. No complete classification has been published for the entire genus, although some preliminary attempts have been offered. In this paper we used tissue sampled from field and herbarium collections of 136 species for genomic sequencing to determine the phylogenetic patterns within Heliconia, which then served as the basis for a new evolutionary classification of the genus. This new classification, which is based on extensive field work and the phylogenomic insights provided here, includes 187 currently recognized species. The new classification of Heliconia is composed of 17 sections in five subgenera with all groups well-supported in the phylogenomic analysis. Four subgenera are each composed of two sections and one subgenus includes nine sections. One subgenus and 10 sections are described as new.